GROWTH AND PHYSIOLOGY OF Balfourodendron riedelianum SEEDLINGS IN THE NURSERY AND IN THE FIELD - Turchetto, Felipe; Mezzomo, Jessé Caletti; Araujo, Maristela Machado; Griebeler, Adriana Maria; Berghetti, Álvaro Luís Pasquetti; Barbosa, Felipe Manzoni (Floresta, 2019)
The present study aimed to determine the effect of different container volumes and doses of controlled release fertilizer (CRF) on the morphophysiological aspects of Balfourodendron riedelianum seedlings in the nursery and verify if these responses were replicated in the field. For the production of seedlings in nursery, three container volumes (180 and 280 cm³ polypropylene tubes and 500 cm³ plastic bags) and four doses of CRF (0, 4, 8, and 12 g L-1 of substrate) were tested, and the seedlings were grown for 240 days. At the end of the nursery period, the following parameters were measured: height (H); stem diameter (SD); dry mass of shoot, root, and total; root length; leaf area; and chlorophyll fluorescence. The H/SD ratio and the Dickson Quality Index were calculated. The same treatments were evaluated in the field at 540 days after planting. Survival, height, and diameter increase, aerial dry mass, leaf area, chlorophyll a fluorescence and chlorophyll index (a, b and total) were measured. Basic fertilization using CRF had a positive influence on the production of B. riedelianum seedlings. It is recommended to use a 180 cm³ tube and a dose of 12 g L-1 CRF for the production of seedlings. The results obtained in the nursery for the production of seedlings were confirmed to occur in the field.